1992
DOI: 10.1017/s0003356100020729
|View full text |Cite
|
Sign up to set email alerts
|

A note on the effect of wood cellulose level in protein-free diets on the recovery and amino acid composition of endogenous protein collected from the ileum in pigs

Abstract: The effect of fibre level in protein-free diets on the recovery and amino acid composition of endogenous protein collected from the ileum in pigs was studied. Although the Heal nitrogen excretion increased slightly with dietary fibre level, no significant difference was observed on the amino acid recovery between diets containing 30, 60,90 or 120 g wood cellulose per kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…In the current study, ingredient-specific ileal flows of protein (i.e., corrected for flows in casein diet; Figure 1) were affected by dietary components such as dietary fiber, lectins, and condensed tannins, in agreement with studies by Jansman (1993) and Schulze et al (1994). The length of the pretest period has been reported to affect the amount and AA composition of endogenous protein in ileal digesta of pigs (Leterme et al, 1992;Jansman et al, 1993). In the present experiment, the pigs received the diets for 12 d before digesta collection to ensure that the time of adaptation was sufficient to elicit diet-specific responses.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In the current study, ingredient-specific ileal flows of protein (i.e., corrected for flows in casein diet; Figure 1) were affected by dietary components such as dietary fiber, lectins, and condensed tannins, in agreement with studies by Jansman (1993) and Schulze et al (1994). The length of the pretest period has been reported to affect the amount and AA composition of endogenous protein in ileal digesta of pigs (Leterme et al, 1992;Jansman et al, 1993). In the present experiment, the pigs received the diets for 12 d before digesta collection to ensure that the time of adaptation was sufficient to elicit diet-specific responses.…”
Section: Discussionsupporting
confidence: 87%
“…We used Solkafloc (purified cellulose) to balance the diets for total cellulose, and this included some cellulose addition to our casein control diet. However, because purified cellulose does not affect endogenous protein ileal losses (de Lange et al, 1989;Furuya and Kaji, 1992;Leterme et al, 1992), the casein control diet can be used to estimate basal endogenous protein flow. Therefore, the amount, which represents minimal values, and AA composition of endogenous protein can be calculated from studies in which the AID of protein in casein has been determined (Kies et al, 1986;Furuya and Kaji, 1989;Jansman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that the dietary inclusion of water-insoluble fiber depressed the apparent ileal digestibility values of CP and AA (Graham et al 1986;Li et al 1994;Schulze et al 1994;Lenis et al 1996). The lower ileal digestibility values of CP and AA with increasing water-insoluble fiber content may be attributed to an increase in the rate of passage of digesta (Stanogias and Pearce 1985) and increased distal ileal losses of endogenous CP and AA (Sauer et al 1977;Taverner et al 1981;De Lange et al 1989;Furuya and Kaji 1992;Leterme et al 1992). Recently, Huang (1997) in studies with wheat shorts demonstrated that considerable proportions of CP and AA were associated with NDF and were of low digestibility.…”
Section: Resultsmentioning
confidence: 99%